2016
DOI: 10.1007/s12539-016-0184-5
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Epitope-Focused Vaccine by Targeting E6 and E7 Conserved Protein Sequences: An Immuno-Informatics Approach in Human Papillomavirus 58 Isolates

Abstract: Human papillomavirus (HPV) is a DNA virus that belongs to the papillomavirus family and is capable of infecting humans. Currently, few vaccines are available to prevent infection by HPV. However, they are not so much effective and provide little benefit to women who have already been infected with HPV. The aim of this study was to design epitope-based vaccines of HPV58 by targeting E6 and E7 proteins of HPV58. Proteomic sequences were retrieved from different isolates at different time periods and later analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Conservancy analysis showed that five regions of HPV16,18 L1 protein (8-22, 95-132, 307-342, 398-425 and 449-473) and four regions of HPV16,18 L2 protein (11-40, 54-76, 96-120 and 278-305) were more conserved among other subtypes and could be analyzed as an immunoinformatics input. In B-cell epitope prediction, L1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] , L1 408-421 , L1 404-417 , L2 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] , L2 100-113 , L2 94-107 and L2 57-70 had the highest epitope prediction scores. Unfortunately, a reliable method for prediction of B-cell epitope has not been revealed up to now and the sensitivity and specificity of existing methods were very low (the specificity and sensitivity of this method were 0.57 and 0.58, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservancy analysis showed that five regions of HPV16,18 L1 protein (8-22, 95-132, 307-342, 398-425 and 449-473) and four regions of HPV16,18 L2 protein (11-40, 54-76, 96-120 and 278-305) were more conserved among other subtypes and could be analyzed as an immunoinformatics input. In B-cell epitope prediction, L1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] , L1 408-421 , L1 404-417 , L2 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] , L2 100-113 , L2 94-107 and L2 57-70 had the highest epitope prediction scores. Unfortunately, a reliable method for prediction of B-cell epitope has not been revealed up to now and the sensitivity and specificity of existing methods were very low (the specificity and sensitivity of this method were 0.57 and 0.58, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In L1 protein, L1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] (EATVYLPPVPVSKVV-type16), L1 408-421 (PPPGGTLEDTYRFV-type16) and L1 404-417 (NFGVPPPPTTSLVD-type 18) epitopes had the best B cell epitope identification scores. For L2 protein, L2 [22][23][24][25][26][27][28][29][30][31][32][33][34][35] (KQSGTCPPDVVPKV-type18), L2 100-113 (PSDPSIVSLVEETS-type16), L2 94-107 (EPVGPTDPSIVTLI-type18) and L2 [57][58][59][60][61][62][63][64][65][66][67][68][69][70] (GLGIGTGSGTGGRT-type16) epitopes showed the highest epitope identification score between their own protein sequences.…”
mentioning
confidence: 99%
“…Sabah confirmed the peptide region for the E7 protein ranged from27 to 33amino acids and a 9-m epitopes, SSDEDEIGL, in HPV58 E7 were the most potential T cell epitope. And the peptide sequences could interact with as many as seven MHC-1 alleles and showed population coverage up to 90.31% (26). The CTL epitope for the HPV E6 and E7 antigens were screened by acid elution or the use of synthetic overlapping peptides.…”
Section: Discussionmentioning
confidence: 99%
“…91 Conserved epitopes provide powerful immunization for prolonged period. Sabah et al 92 found that the single 9mer CTL epitope ETSVHEIEL was conserved (100%) in all E6 proteins of HPV58 isolates. While designing an epitope-based vaccine, the use of conserved epitopes may be helpful to provide broader cross-protection across multiple strains.…”
Section: Discussionmentioning
confidence: 99%
“…Among the five epitopes of E6 protein, RTEVYQFAF [41][42][43][44][45][46][47][48][49] and YSRIRE-LRY [72][73][74][75][76][77][78][79][80] were predicted to have binding affinity for HLA-A*(32:01, 29:02) and HLA-B*58: 01 MHC class I alleles (Table 1D). Out of 13 MHC-binding E7 peptides (Table 1E), STLSFVCPW [93][94][95][96][97][98][99][100][101] (HLA-A*32:01, HLA-B*58:01, HLA-B*57:01), LQQLFLSTL [87][88][89][90][91][92][93][94][95] (HLA-A*02:06), and QLFLSTLSF [89][90][91][92][93][94][95][96][97] (HLA-B*15:02, HLA-B*15:01, HLA-A*32:01) were predicted to have a binding affinity of IC 50 <200 nm. Furthermore, three out of seven epitopes of L1 protein, such as HVEEYDLQF…”
Section: Cd8 + Ctl Epitopesmentioning
confidence: 99%